Adhesive composition, adhesive and preparation method and application thereof

By using an adhesive composition containing terminal hydroxyl polyalkylsiloxane, modified hexagonal boron nitride, crosslinking agent and coupling agent in offshore photovoltaic project, the corrosion resistance problem of offshore photovoltaic project in high salt spray environment is solved, and the service life of photovoltaic modules is significantly extended.

CN118085803BActive Publication Date: 2025-04-22TRINA SOLAR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410379297.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-04-22
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

Offshore photovoltaic projects are facing a high salt spray environment, and existing silicone adhesives cannot meet the components' salt spray resistance requirements, resulting in corrosion and shortening of the photovoltaic module's service life.

Method used

A adhesive composition is provided, including end-hydroxy polyalkyl siloxane, modified hexagonal boron nitride, crosslinking agent and coupling agent, and grafting hexagonal boron nitride through an aminosilane coupling agent to enhance interface compatibility and form a dense network structure to improve corrosion resistance.

Benefits of technology

The adhesive composition significantly improves the protection performance against salt spray, extends the service time of offshore photovoltaic modules, and ensures the stability and functionality of the modules in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118085803B_ABST
    Figure CN118085803B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of organic silicon adhesives, and specifically relates to an adhesive composition, an adhesive, and a preparation method and application thereof. The adhesive composition comprises the following components: 45 to 60 parts of hydroxyl-terminated polyalkylsiloxane, 0.5 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of a crosslinking agent, and 0.1 to 1 part of a coupling agent; wherein the modified hexagonal boron nitride is an aminosilane coupling agent grafted hexagonal boron nitride. The adhesive composition provided by the present application is prepared by reasonably proportioning the weight proportions of each component, and applying the aminosilane coupling agent grafted hexagonal boron nitride nanosheets to the adhesive composition, so that the aminosilane coupling agent can be grafted to the hexagonal boron nitride nanosheets through the silane group, and the amino group therein can bond with the hydroxyl-terminated polyalkylsiloxane, thereby reducing microscopic defects such as voids and cracks, thereby reducing the penetration path of corrosive substances such as salt spray, thereby improving the corrosion resistance of the adhesive composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of silicone adhesives, and in particular to an adhesive composition, an adhesive, and a preparation method and application thereof. Background Art

[0002] With the acceleration of energy conservation, emission reduction, low carbon and environmental protection, sustainable clean energy has become the main focus. Due to the advantages of open and unobstructed sea surface, long sunshine and full use of reflected light from the water surface, offshore photovoltaic projects have received widespread attention.

[0003] However, offshore photovoltaic projects face complex and harsh service environments that are different from those on land, such as strong winds and waves, typhoons, high salt fog, and high humidity. Among them, ions in salt fog, such as chloride ions and sodium ions, are highly corrosive. If they enter the interior of photovoltaic modules, they will seriously corrode the batteries and affect the normal use of the modules. Adhesives, as a bonding material with excellent resistance to cold and heat, durability, and sealing properties, are widely used in the packaging of photovoltaic modules. However, based on the high salt fog service environment faced by offshore photovoltaics, the requirements for module packaging are further strengthened. The currently used organic silicone adhesives generally cannot meet the requirements of module resistance to salt fog. Summary of the invention

[0004] Based on this, the present application provides an adhesive composition, an adhesive, and a preparation method and application thereof. The adhesive composition provided in the present application has excellent salt spray resistance and can be widely used in the packaging of photovoltaic modules, thereby effectively extending the service life of offshore photovoltaic modules.

[0005] In a first aspect of the present application, an adhesive composition is provided, comprising the following components, in parts by weight: 45 to 60 parts of hydroxyl-terminated polyalkylsiloxane, 0.5 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of a crosslinking agent, and 0.1 to 1 part of a coupling agent;

[0006] Wherein, the structure of the hydroxy-terminated polyalkylsiloxane is , n is selected from a positive integer between 0 and 10; R1, R2, R3, R4, R5 and R6 are each independently selected from a C1 to C6 alkyl group;

[0007] The modified hexagonal boron nitride is hexagonal boron nitride grafted with an aminosilane coupling agent.

[0008] In one embodiment, the aminosilane coupling agent grafted hexagonal boron nitride is formed by grafting hydroxylated hexagonal boron nitride with an aminosilane coupling agent; and / or,

[0009] The aminosilane coupling agent includes one or more of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyldimethoxysilane.

[0010] In one embodiment, R1, R2, R3, R4, R5 and R6 are each independently selected from methane or ethyl.

[0011] In one embodiment, the viscosity of the hydroxy-terminated polyalkylsiloxane at 25° C. is 30,000 cps to 80,000 cps.

[0012] In one embodiment, the crosslinking agent includes tetrabutyl ketone oxime silane and vinyl tributyl ketone oxime silane in a mass ratio of (1-2):1.

[0013] In one embodiment, the coupling agent includes γ-aminopropyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of (1~2):1.

[0014] In one embodiment, the adhesive composition further comprises other additives, and the other additives include one or more of fillers, whitening powder and catalysts.

[0015] In one embodiment, in the adhesive composition, the filler is 40 to 50 parts by weight.

[0016] In one embodiment, in the adhesive composition, the whitening powder is 0.5 to 1 part by weight.

[0017] In one embodiment, in the adhesive composition, the catalyst is present in an amount of 0.05 to 0.2 parts by weight.

[0018] In one embodiment, the filler includes one or more of talc, calcium carbonate, barium sulfate and silicon dioxide.

[0019] In one embodiment, the whitening powder includes one or more of titanium dioxide, zinc oxide, lead oxide and magnesium oxide.

[0020] In one embodiment, the catalyst includes one or more of dibutyltin dilaurate and dibutyltin dichloride.

[0021] A second aspect of the present application provides a method for preparing an adhesive, comprising the following steps:

[0022] Take aminosilane coupling agent grafted hexagonal boron nitride, mix the raw material components according to weight proportions, and prepare the adhesive.

[0023] In one embodiment, the preparation steps of the aminosilane coupling agent grafted hexagonal boron nitride include:

[0024] dissolving the aminosilane coupling agent in an organic solvent to prepare a grafting solution;

[0025] The hydroxylated hexagonal boron nitride is mixed with the grafting liquid, and a grafting reaction is performed to prepare the aminosilane coupling agent grafted hexagonal boron nitride.

[0026] In one embodiment, the mass fraction of the aminosilane coupling agent in the grafting solution is 0.5% to 3%.

[0027] In one embodiment, the process parameters of the grafting reaction include: the grafting temperature is 15°C~30°C.

[0028] In one embodiment, the preparation steps of the hydroxylated hexagonal boron nitride include:

[0029] The hexagonal boron nitride nanosheets are mixed with an alkaline solution and subjected to a surface hydroxylation reaction to prepare hydroxylated hexagonal boron nitride.

[0030] In one embodiment, the molar concentration of hydroxyl groups in the alkaline solution is 4 mol / L to 6 mol / L.

[0031] In one embodiment, the process parameters of the surface hydroxylation reaction include: the temperature of the surface hydroxylation reaction is 70°C~90°C.

[0032] In one embodiment, the steps of preparing the hexagonal boron nitride nanosheets include:

[0033] The ionic liquid is dissolved in a mixed solution of an organic solvent and water, and ultrasonically dispersed to prepare a dispersion;

[0034] After centrifuging the dispersion, the supernatant was collected;

[0035] After the supernatant is filtered, the hexagonal boron nitride nanosheets are prepared.

[0036] In one embodiment, the mass fraction of the ionic liquid in the dispersion is 3% to 6%.

[0037] In one embodiment, the ionic liquid includes one or more of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium hexafluorophosphate and 1-hexyl-3-methylimidazolium hexafluorophosphate.

[0038] In one embodiment, the centrifugal process parameters include: a rotation speed of 3000r / min~5000r / min.

[0039] In one embodiment, the filtration step uses a filter membrane with a pore diameter of 0.15 μm to 0.25 μm.

[0040] The third aspect of the present application provides an adhesive, wherein the raw materials for preparing the adhesive include the adhesive composition described in any embodiment of the first aspect of the present application, or the adhesive is prepared by any preparation method of the second aspect of the present application.

[0041] The fourth aspect of the present application provides a use of the adhesive described in the third aspect of the present application in the preparation of photovoltaic modules.

[0042] The fifth aspect of the present application provides a photovoltaic module, characterized in that it includes a curing agent for the adhesive as described in the fourth aspect of the present application.

[0043] The adhesive composition provided in the present application is prepared by reasonably proportioning the weight proportions of the components and applying the aminosilane coupling agent grafted to the hexagonal boron nitride in the adhesive composition, so that the aminosilane coupling agent can be grafted to the hexagonal boron nitride through the silane group, and the amino group therein can bond with the terminal hydroxyl polyalkyl siloxane, so that the silane coupling agent can act as a bridge between the terminal hydroxyl polyalkyl siloxane and the modified hexagonal boron nitride to enhance the compatibility of the interface; this improved interfacial compatibility helps to form a denser and more uniform network structure, thereby reducing microscopic defects such as voids and cracks, and further reducing the penetration path of corrosive substances such as salt spray, thereby improving the corrosion resistance of the adhesive composition.

[0044] In addition, the combined effect of terminal hydroxyl polyalkylsiloxane, crosslinking agent and coupling agent can effectively increase the crosslinking density of adhesive. Adhesives with high crosslinking density have better chemical stability and mechanical properties, which enables the adhesive composition to maintain good structural integrity and functionality when facing harsh environments such as salt spray, and can effectively increase the penetration resistance of salt spray and other corrosive media, reducing the risk of salt spray corrosion on the adhesive matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 A process flow chart of the method for preparing the adhesive composition provided in this application;

[0047] Figure 2 A reaction flow chart of the preparation method of aminosilane coupling agent grafted hexagonal boron nitride provided in this application;

[0048] Figure 3 This is a process flow chart of the preparation method of aminosilane coupling agent grafted hexagonal boron nitride provided in this application. DETAILED DESCRIPTION

[0049] The adhesive composition, adhesive and preparation method and application of the present application are further described in detail below in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0050] The term "alkyl" refers to a saturated hydrocarbon group containing primary (normal) carbon atoms, or secondary carbon atoms, or tertiary carbon atoms, or quaternary carbon atoms, or a combination thereof. A phrase containing the term, for example, "C1-C6 alkyl" refers to an alkyl group containing 1 to 6 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-propyl, n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-butyl, n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), tert-butyl yl (1,1-dimethylethyl, 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2).

[0051] In the first aspect of the present application, an adhesive composition is provided, which comprises the following components, measured in parts by weight: 45 to 60 parts of terminal hydroxyl polyalkyl siloxane, 0.5 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of a cross-linking agent, and 0.1 to 1 part of a coupling agent; the modified hexagonal boron nitride is hexagonal boron nitride grafted with an aminosilane coupling agent.

[0052] As the main component of the adhesive composition, the hydroxyl group of the terminal hydroxyl polyalkyl siloxane can react with the crosslinking agent, coupling agent, modified hexagonal boron nitride, etc. in the adhesive composition to form a three-dimensional network structure, which not only increases the mechanical strength of the material, but also improves the chemical bonding force at the bonding interface, thereby enhancing the bonding strength. To ensure the crosslinking between the components of the adhesive composition, while avoiding the decrease in the mechanical properties of the adhesive composition caused by the introduction of too many soft segments. Preferably, the weight parts of the terminal hydroxyl polyalkyl siloxane are 45 to 60 parts. It can be understood that the weight parts of the terminal hydroxyl polyalkyl siloxane can be selected from any value between 45 and 60 parts, specifically, the weight parts of the terminal hydroxyl polyalkyl siloxane include but are not limited to 46 parts, 48 ​​parts, 50 parts, 51 parts, 52 parts, 53 parts, 55 parts, 58 parts or 60 parts.

[0053] The addition of modified hexagonal boron nitride can improve its interfacial compatibility with terminal hydroxyl polyalkylsiloxane and achieve better dispersibility; at the same time, the uniformly dispersed modified hexagonal boron nitride can effectively bear and transfer stress, and improve the mechanical properties of the adhesive composition such as tensile strength, elastic modulus and hardness. Furthermore, modified hexagonal boron nitride synergizes with crosslinking agents and coupling agents as well as terminal hydroxyl polyalkylsiloxane to effectively improve the density and structural integrity of the adhesive composition, reduce the penetration of salt and moisture, and thus effectively improve the corrosion resistance of the adhesive composition. Preferably, the weight proportion of modified hexagonal boron nitride is 0.5 to 6 parts. Specifically, the weight proportions of modified hexagonal boron nitride include but are not limited to 0.6 parts, 0.8 parts, 1 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 5.8 parts or 6 parts.

[0054] The crosslinking agent can initiate or promote the crosslinking reaction between molecules to form a stable three-dimensional network structure. The weight parts of the crosslinking agent can be selected from any value between 2 parts and 5 parts. Specifically, the weight parts of the crosslinking agent include but are not limited to 2.1 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.1 parts, 3.2 parts, 3.5 parts, 3.6 parts, 3.8 parts, 4 parts, 4.1 parts, 4.3 parts, 4.5 parts, 4.8 parts or 5 parts.

[0055] The coupling agent can induce bonding between molecules of different substances such as terminal hydroxyl polyalkylsiloxane and modified hexagonal boron nitride to improve the compatibility and bonding strength between the components, thereby effectively increasing the penetration resistance of salt spray and other corrosive media. Preferably, the weight portion of the coupling agent is 0.1 part to 1 part. Specifically, the weight portion of the coupling agent includes but is not limited to 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part.

[0056] In one example, the structure of the hydroxy-terminated polyalkylsiloxane is , n is selected from a positive integer between 0 and 10; R1, R2, R3, R4, R5 and R6 are each independently selected from a C1 to C6 alkyl group. The flexible siloxane main chain structure of the terminal hydroxyl polyalkylsiloxane, when added to the adhesive composition, can significantly improve the flexibility and ductility of the final product to ensure that the adhesive composition has excellent elongation at break. Preferably, the R1, R2, R3, R4, R5 and R6 are each independently selected from a methane group or an ethyl group. More preferably, the terminal hydroxyl polyalkylsiloxane includes one or more of terminal hydroxyl polydimethylsiloxane and terminal hydroxyl polydiethylsiloxane.

[0057] In one example, the aminosilane coupling agent grafted hexagonal boron nitride is formed by grafting hydroxylated hexagonal boron nitride with an aminosilane coupling agent; and / or,

[0058] The aminosilane coupling agent includes one or more of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyldimethoxysilane. Optionally, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane can be commercially available KH792 model.

[0059] In one example, the viscosity of the terminal hydroxyl polyalkyl siloxane at 25°C is 30000cps~80000cps. Limiting the viscosity of the terminal hydroxyl polyalkyl siloxane can ensure the bonding performance of the adhesive composition and enhance its adhesion to the substrate. Specifically, the viscosity of the terminal hydroxyl polyalkyl siloxane at 25°C includes but is not limited to 35000 cps, 38000cps, 40000 cps, 42000 cps, 45000 cps, 48000 cps, 50000 cps, 52000 cps, 55000 cps, 60000 cps, 70000 cps or 80000 cps. It is understandable that the terminal hydroxyl polyalkyl siloxane with a viscosity of 30000cps~80000cps at 25°C can be applied to the adhesive composition of the present application, and suitable raw material models include but are not limited to commercially available 107 glue. Preferably, the crosslinking agent comprises tetrabutyl ketoxime silane and vinyl tributyketoxime silane in a mass ratio of (1~2):1. The active groups oxime and alkenyl contained in tetrabutyl ketoxime silane and vinyl tributyketoxime silane can react with the terminal hydroxyl polyalkylsiloxane to form a three-dimensional crosslinked network structure, enhance the cohesion of the adhesive composition, and reduce the space and opportunity for salt spray to penetrate into the adhesive composition. Specifically, the mass ratio of tetrabutyl ketoxime silane and vinyl tributyketoxime silane includes but is not limited to 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1.

[0060] To effectively ensure the bonding between molecules of different substances such as terminal hydroxyl polyalkylsiloxane and modified hexagonal boron nitride. In one example, the coupling agent includes γ-aminopropyltrimethoxysilane and γ-(2, 3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of (1~2):1. Specifically, the mass ratio of γ-aminopropyltrimethoxysilane and γ-(2, 3-epoxypropoxy)propyltrimethoxysilane includes but is not limited to 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1. It can be understood that commercially available γ-aminopropyltrimethoxysilane and γ-(2, 3-epoxypropoxy)propyltrimethoxysilane can be used as coupling agents of the present application. The models of γ-aminopropyltrimethoxysilane include but are not limited to KH540; the models of γ-(2,3-epoxypropoxy)propyltrimethoxysilane include but are not limited to KH560.

[0061] In one example, the D50 particle size of the hexagonal boron nitride powder is 1 μm to 5 μm. It can be understood that commercially available hexagonal boron nitride powders with a particle size of 1 μm to 5 μm can be used as raw materials for the adhesive composition of the present application.

[0062] In one example, the adhesive composition further includes other additives, and the other additives include one or more of fillers, whitening powder and catalysts.

[0063] The addition of fillers can increase the viscosity and rheology of the adhesive composition, making it easier to apply on the surface of the bonded substrate, and can effectively fill small gaps to effectively isolate salt spray. In one example, in the adhesive composition, the filler is 40 to 50 parts by weight. Specifically, the weight of the filler includes but is not limited to 42 parts, 43 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts.

[0064] In order to promote the curing reaction of the adhesive composition, accelerate the hydrolysis and condensation of the adhesive composition with moisture in the air, and shorten the curing time. In one example, in the adhesive composition, the catalyst is 0.05 to 0.2 parts by weight. Specifically, the weight parts of the catalyst include but are not limited to 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.17 parts, 0.18 parts, 0.19 parts or 0.2 parts.

[0065] The addition of whitening powder can improve the aesthetics, hiding power and weather resistance of the adhesive composition, and improve the stability of the adhesive composition under ultraviolet light. In one example, in the adhesive composition, the whitening powder is 0.5 to 1 part by weight. Specifically, the weight of the whitening powder includes but is not limited to 0.6, 0.7, 0.8, 0.9 or 1 part.

[0066] In one example, the filler includes one or more of talc, calcium carbonate, barium sulfate and silicon dioxide.

[0067] In one specific example, the particle size of the filler is 2 μm to 8 μm. Specifically, the particle size of the filler includes but is not limited to 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.

[0068] In one example, the whitening powder includes one or more of titanium dioxide, zinc oxide, lead oxide and magnesium oxide.

[0069] In one specific example, the particle size of the whitening powder is 2 μm to 8 μm. Specifically, the particle size of the whitening powder includes but is not limited to 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.

[0070] In one example, the catalyst includes one or more of dibutyltin dilaurate and dibutyltin dichloride.

[0071] In one specific example, the adhesive composition includes the following components, measured in parts by weight: 45 to 60 parts of terminal hydroxyl polyalkyl siloxane, 0.5 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of cross-linking agent, 0.1 to 1 part of coupling agent, and 40.55 to 51.2 parts of other additives.

[0072] In one more specific example, the adhesive composition includes the following components, measured in parts by weight: 45 to 60 parts of terminal hydroxyl polyalkyl siloxane, 0.5 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of cross-linking agent, 0.1 to 1 part of coupling agent, 40 to 50 parts of filler, 0.05 to 0.2 parts of catalyst, and 0.5 to 1 part of whitening powder.

[0073] A second aspect of the present application provides a method for preparing an adhesive, comprising the following steps:

[0074] Take aminosilane coupling agent grafted hexagonal boron nitride, mix the raw material components according to weight proportions, and prepare the adhesive.

[0075] It can be understood that the above-mentioned preparation raw materials are the components of the adhesive composition mentioned in the first aspect of the present application.

[0076] In one specific example, the method for preparing the adhesive comprises the following steps:

[0077] a. Taking aminosilane coupling agent grafted hexagonal boron nitride, stirring and mixing the aminosilane coupling agent grafted hexagonal boron nitride and terminal hydroxyl polyalkylsiloxane to prepare a mixture;

[0078] b. Dehydrating the mixture to prepare a semi-finished base material;

[0079] c. Add a coupling agent and a cross-linking agent into the semi-finished base material and mix them, and after discharging the materials, prepare the adhesive.

[0080] In one example, in step a, the process parameters for stirring and mixing the aminosilane coupling agent grafted with hexagonal boron nitride and the hydroxy-terminated polyalkylsiloxane include: a rotation speed of 250 rpm to 400 rpm.

[0081] In one example, in step b, the process parameters of the dehydration treatment include: heating to 90°C~150°C, and performing the dehydration treatment at a pressure of -0.1MPa~-0.05MPa. Specifically, the temperature of the dehydration treatment includes but is not limited to 100°C, 105°C, 108°C, 109°C, 110°C, 111°C, 112°C, 115°C, 120°C, 130°C, 140°C or 150°C. The pressure of the dehydration treatment includes but is not limited to -0.1MPa, -0.098 MPa, -0.095 MPa, -0.093 MPa, -0.092 MPa, -0.091 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa or -0.05 MPa.

[0082] In one example, in step c, the specific steps of adding a coupling agent and a crosslinking agent to the semi-finished base material for mixing include: controlling the pressure to -0.1MPa~-0.05MPa and the rotation speed to 250rpm~400rpm, and adding the crosslinking agent and the coupling agent to the semi-finished base material.

[0083] It is understood that if the adhesive contains other additives, the filler and the whitening powder are optionally mixed together in step a. The catalyst is mixed in step c. For example, see Figure 1 The preparation method of the adhesive containing other additives includes the following steps: a. taking aminosilane coupling agent grafted hexagonal boron nitride, stirring and mixing the aminosilane coupling agent grafted hexagonal boron nitride, terminal hydroxyl polyalkylsiloxane, whitening powder and filler to prepare a mixture; b. dehydrating the mixture to prepare a semi-finished base material; c. adding a coupling agent, a cross-linking agent and a catalyst to the semi-finished base material and mixing, and after discharging, preparing the adhesive.

[0084] Hexagonal boron nitride is a graphite-like two-dimensional lamellar structure material with excellent heat resistance, thermal stability and thermal conductivity. However, the surface of hexagonal boron nitride is very stable and has few active groups, making it difficult to modify.

[0085] Based on this, see Figure 2 and Figure 3 The present application provides a method for preparing aminosilane coupling agent grafted hexagonal boron nitride, comprising the following steps:

[0086] S10, dissolving the ionic liquid in a mixed solution of an organic solvent and water, adding hexagonal boron fluoride powder to the mixed solution, and ultrasonically dispersing the mixed solution to prepare a dispersion;

[0087] S20, centrifuging the dispersion and collecting the supernatant;

[0088] S30, filtering the supernatant to prepare the hexagonal boron nitride nanosheets;

[0089] S40, mixing the hexagonal boron nitride nanosheets with an alkaline solution, and performing a surface hydroxylation reaction to prepare hydroxylated hexagonal boron nitride;

[0090] S50, dissolving the aminosilane coupling agent in an organic solvent to prepare a grafting solution;

[0091] S60, mixing the hydroxylated hexagonal boron nitride with the grafting liquid, and performing a grafting reaction to prepare the aminosilane coupling agent-grafted hexagonal boron nitride.

[0092] In one example, in step S10, the mass fraction of the ionic liquid in the dispersion is 3% to 6%. The mass fraction of the ionic liquid in the dispersion is limited to 3% to 6%, wherein the ionic liquid can interact with hexagonal boron nitride, and the cations and anions in the ionic liquid can be covered on the surface of the hexagonal boron nitride in a charge-shielded manner, and the charges shielded on the surface reduce the adhesion between the hexagonal boron nitride layers, thereby achieving effective peeling. Specifically, in step S10, the mass fraction of the ionic liquid in the dispersion includes but is not limited to 3.3%, 3.5%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.5%, 4.8% or 5%.

[0093] Further, in step S10, the mixing volume ratio of the organic solvent and water in the dispersion is (1-3): 1. Specifically, the mixing volume ratio of the organic solvent and water in the dispersion includes but is not limited to 1:1, 1.1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.1:1, 2.2:1, 2.5:1, 2.8:1 or 3:1.

[0094] In one example, in step S10, the ionic liquid includes one or more of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium hexafluorophosphate, and 1-hexyl-3-methylimidazolium hexafluorophosphate.

[0095] In one example, in step S10, the mass volume concentration of hexagonal boron nitride powder in the mixed solution is 5 mg / mL to 10 mg / mL. Specifically, the mass volume concentration of hexagonal boron nitride in the mixed solution includes but is not limited to 5 mg / mL, 6 mg / mL, 8 mg / mL or 10 mg / mL.

[0096] In one example, in step S10, the process parameters of ultrasonic dispersion include: ultrasonic temperature of 15° C. to 30° C., and ultrasonic time of 10 h to 24 h.

[0097] In one example, in step S20, the centrifugal process parameters include: a rotation speed of 3000 r / min to 5000 r / min. Further, a centrifugal time of 10 min to 40 min.

[0098] In order to effectively separate the hexagonal boron nitride nanosheets and ensure the structural integrity of the nanosheets. In one example, in step S30, the filtration step uses a filter membrane with a pore diameter of 0.15μm to 0.25μm. Specifically, the pore diameter of the filter membrane includes but is not limited to 0.18μm, 0.19μm, 0.2μm, 0.21μm, 0.22μm, 0.23μm or 0.25μm.

[0099] In order to increase the degree of hydroxylation and improve the chemical stability of the modified hexagonal boron nitride, in one example, in step S40, the molar concentration of the hydroxyl group in the alkaline solution is 4 mol / L to 6 mol / L.

[0100] In one example, in step S40, the mass volume ratio of the hexagonal boron nitride nanosheets and the alkaline solution is (20mg~50mg):1mL. It can be understood that when the hexagonal boron nitride nanosheets and the alkaline solution are mixed, the mass and volume are correspondingly expanded, which is also within the scope of protection of the present application. Here, it can be exemplified as (20g~50g):1L. Specifically, the mass volume ratio of the hexagonal boron nitride nanosheets and the alkaline solution includes but is not limited to 25mg:1mL, 30mg:1mL, 35mg:1mL, 40mg:1mL, 45mg:1mL or 50mg:1mL.

[0101] To introduce hydroxyl groups on the surface of hexagonal boron nitride and improve the reaction efficiency. In one example, in step S40, the process parameters of the surface hydroxylation reaction include: the temperature of the surface hydroxylation reaction is 70°C to 90°C. Specifically, the temperature for the surface hydroxylation reaction includes but is not limited to 75°C, 78°C, 80°C, 82°C, 85°C, 88°C or 90°C. In one example, in step S40, the time for the surface hydroxylation reaction is 18h to 24h.

[0102] In one example, in step S50, the mass fraction of the aminosilane coupling agent in the grafting solution is 0.5% to 3%. Specifically, the mass fraction of the aminosilane coupling agent in the grafting solution includes but is not limited to 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.7%, 2.8%, 2.9% or 3%. In one example, in step S60, the process parameters of the grafting reaction include: the grafting temperature is 15°C to 30°C. The temperature of the grafting reaction includes but is not limited to 16°C, 17°C, 20°C, 22°C, 25°C, 27°C, 29°C or 30°C. In one example, in step S60, the time for the grafting reaction is 0.5h to 3h.

[0103] In one example, in step S60, the mass volume ratio of the hydroxylated hexagonal boron nitride and the grafting liquid is (30 mg~60 mg): 1 mL. By reasonably controlling the mass fraction of the aminosilane coupling agent in the grafting liquid, the temperature of the grafting reaction, and the volume ratio of the hydroxylated hexagonal boron nitride and the grafting liquid, it is possible to ensure that the aminosilane coupling agent is successfully grafted to the surface of the hexagonal boron nitride, and achieve the co-modification of hydroxyl groups and aminosilane coupling agents. Specifically, the mass volume ratio of the hydroxylated hexagonal boron nitride and the grafting liquid includes but is not limited to 30 mg: 1 mL, 40 mg: 1 mL, 45 mg: 1 mL, 50 mg: 1 mL, 55 mg: 1 mL or 60 mg: 1 mL.

[0104] In a more specific example, the preparation method of the aminosilane coupling agent grafted hexagonal boron nitride comprises the following steps:

[0105] S100, dissolving the ionic liquid in a mixed solution of an organic solvent and water in a volume ratio of (1-3):1, adding hexagonal boron fluoride powder, and ultrasonically dispersing at 15°C-30°C for 10h-24h to prepare a dispersion, wherein the mass fraction of the ionic liquid in the dispersion is 3%-6%;

[0106] S200, centrifuging the dispersion at a speed of 3000 r / min to 5000 r / min for 10 min to 40 min, and collecting the supernatant;

[0107] S300, filtering the supernatant with a filter membrane having a pore diameter of 0.15 μm to 0.25 μm, and washing with acetone to prepare the hexagonal boron nitride nanosheets;

[0108] S400, mixing hexagonal boron nitride nanosheets and an alkaline solution having a molar concentration of hydroxyl group of 4 mol / L to 6 mol / L by ultrasonic dispersion at room temperature for 1 h, stirring at 70° C. to 90° C. for 18 h to 24 h for surface hydroxylation reaction, washing and filtering, and preparing hydroxylated hexagonal boron nitride;

[0109] S500, dissolving the aminosilane coupling agent in an organic solvent to prepare a grafting solution, wherein the mass fraction of the aminosilane coupling agent in the grafting solution is 0.5% to 3%;

[0110] S600, mixing hydroxylated hexagonal boron nitride with the grafting liquid, mixing for 0.5 h to 3 h at 15° C. to 30° C. for grafting reaction, washing, drying and grinding to prepare the aminosilane coupling agent grafted hexagonal boron nitride.

[0111] The third aspect of the present application provides an adhesive, including the adhesive composition described in any example of the first aspect of the present application, or prepared by any preparation method of the second aspect.

[0112] The fourth aspect of the present application provides a use of the adhesive described in the third aspect of the present application in preparing components.

[0113] The fifth aspect of the present application provides a photovoltaic module, comprising a cured adhesive of the adhesive as described in the third aspect of the present application. Under the action of a catalyst, the active ketoxime group in the crosslinking agent of the adhesive provided by the present application reacts with water vapor in the air to release ketoxime and silanol, and the hydroxyl group in the silanol reacts with the hydroxyl group of the terminal hydroxyl polyalkylsiloxane. At the same time, the amino group in the modified hexagonal boron nitride can also bond with the terminal hydroxyl polyalkylsiloxane, thereby forming a crosslinked network system to obtain a cured adhesive.

[0114] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0115] [raw material]

[0116] Hexagonal boron nitride powder, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., particle size: 1 μm;

[0117] 1-Butyl-3-methylimidazolium hexafluorophosphate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0118] Aminosilane coupling agent: purchased from Hubei New Blue Sky New Materials Co., Ltd., model KH792;

[0119] Hydroxyl-terminated polydimethylsiloxane: purchased from Zhejiang Xin'an Chemical Industry Group Co., Ltd., model: 107 glue, viscosity 50000cps;

[0120] Calcium carbonate: particle size 2~8μm;

[0121] Titanium dioxide: particle size 2~8μm;

[0122] Cross-linking agent tetrabutyl ketone oxime silane: purchased from Hubei New Blue Sky New Materials Co., Ltd.

[0123] Cross-linking agent vinyl trisbutyl ketoxime silane: purchased from Hubei New Blue Sky New Materials Co., Ltd.;

[0124] Coupling agent γ-aminopropyltrimethoxysilane: purchased from Hubei New Blue Sky New Materials Co., Ltd., model KH540;

[0125] Coupling agent γ-(2, 3-epoxypropoxy)propyltrimethoxysilane: purchased from Hubei New Blue Sky New Materials Co., Ltd., model KH560;

[0126] Catalyst dibutyltin disilicate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0127] Preparation Example 1

[0128] Preparation Example 1 of the present application provides a modified hexagonal boron nitride and a preparation method thereof, comprising the following steps:

[0129] (1) dissolving 1-butyl-3-methylimidazolium hexafluorophosphate in isopropanol to obtain an organic solvent containing an ionic liquid (the mass percentage of 1-butyl-3-methylimidazolium hexafluorophosphate is 5%); mixing the organic solvent containing the ionic liquid and water in a volume ratio of 2:1 to obtain a mixed solution; adding hexagonal boron nitride powder to the mixed solution, wherein the mass volume concentration of the hexagonal boron nitride powder is 8 mg / mL; and ultrasonically dispersing the mixed solution at 25° C. for 12 hours to prepare a dispersion;

[0130] (2) centrifuging the dispersion at 4000 r / min for 30 min and collecting the supernatant;

[0131] (3) The supernatant is vacuum filtered through a filter membrane with a pore diameter of 0.22 μm, washed with acetone, and vacuum dried at 75° C. for 12 h to prepare the hexagonal boron nitride nanosheets;

[0132] (4) ultrasonically dispersing hexagonal boron nitride nanosheets and a 6 mol / L NaOH solution at room temperature for 1 h to obtain a mixed solution, in which the mass volume concentration of hexagonal boron nitride nanosheets is 35 mg / mL; stirring the mixed solution at 80°C for 20 h for surface hydroxylation reaction, cooling the mixed solution to room temperature, washing the solution with deionized water and vacuum filtering until the mixed solution is neutral, thereby obtaining hydroxylated hexagonal boron nitride nanosheets;

[0133] (5) dissolving the aminosilane coupling agent KH792 in anhydrous ethanol to prepare a grafting solution, wherein the mass fraction of the aminosilane coupling agent KH792 in the grafting solution is 1%;

[0134] (6) Mixing hydroxylated hexagonal boron nitride nanosheets with the grafting liquid to obtain a grafting mixed liquid; the mass volume concentration of hydroxylated hexagonal boron nitride nanosheets in the grafting mixed liquid is 50 mg / mL; mixing the grafting mixed liquid at 25° C. for 1 hour for grafting reaction, washing, drying, and grinding to prepare the aminosilane coupling agent grafted hexagonal boron nitride nanosheets.

[0135] Embodiment 1 to Embodiment 3

[0136] Embodiment 1 to embodiment 3 provide an adhesive and a preparation method thereof, comprising the following steps:

[0137] (1) The aminosilane coupling agent grafted hexagonal boron nitride nanosheets prepared in Preparation Example 1, the aminosilane coupling agent grafted hexagonal boron nitride nanosheets, hydroxyl-terminated polydimethylsiloxane, calcium carbonate, and titanium dioxide are put into a vacuum kneader according to weight proportions, and dispersed and stirred at a high speed of 300 rpm to prepare a mixture;

[0138] (2) After the mixed material is heated to 110°C, it is dehydrated at a pressure of -0.092 MPa for 3.5 hours. After dehydration, the machine is stopped to obtain the semi-finished base material;

[0139] (3) Then, the base material cooled to room temperature is added to a double planetary mixer, the pressure is controlled to be -0.092Mpa, the speed is 300rpm, and the cross-linking agent is added with nitrogen pressure relief and stirred at 300rpm for 30min; then, the coupling agent and catalyst are added under the protection of nitrogen pressure relief, and the stirring is continued at the pressure of -0.092Mpa for 20min, and finally, the material is discharged from the elevator under the protection of nitrogen pressure relief, and the prepared adhesive is poured for use. The weight proportions of the raw materials for preparing the adhesives in Examples 1 to 3 are shown in Table 1.

[0140] Comparative Example 1

[0141] The preparation steps of Comparative Example 1 and Example 1 are basically the same, the main difference being that Comparative Example 1 uses the hydroxylated hexagonal boron nitride nanosheets prepared in step (3) of the preparation example; the weight fractions of the various components of the adhesive preparation raw materials in Comparative Example 1 are shown in Table 2.

[0142] Comparative Example 2~Comparative Example 3

[0143] The preparation steps of Comparative Examples 2 to 3 are basically the same as those of Example 1, with the main difference being that no modified hexagonal boron nitride nanosheets are added in Comparative Examples 2 to 3; the weight fractions of the various components of the adhesive preparation raw materials in Comparative Examples 2 to 3 are shown in Table 2.

[0144] Comparative Example 4~Comparative Example 5

[0145] The preparation steps of Comparative Examples 4 to 5 are basically the same as those of Example 1, with the main difference being that the weight fractions of modified hexagonal boron nitride nanosheets and calcium carbonate added in Comparative Examples 4 to 5 are different from those in Example 1; the weight fractions of the various components of the adhesive preparation raw materials in Comparative Examples 4 to 5 are shown in Table 2.

[0146] Table 1

[0147]

[0148] Table 2

[0149]

[0150] The adhesives prepared in the above embodiments and comparative examples were subjected to the following tests:

[0151] (1) Surface drying time: Apply the adhesive on a folded A4 paper, press it tightly and then unfold it to form a butterfly shape. Then wipe the tip of your finger with anhydrous ethanol and gently touch three different parts of the specimen. Repeat the above operation at appropriate intervals until no specimen adheres to your finger. Record the time from the time the adhesive is applied until the specimen no longer adheres to your finger.

[0152] (2) Tensile strength: Refer to GB / T 528 standard to test the tensile strength of the adhesive;

[0153] (3) Elongation at break: Test the elongation at break of adhesives according to GB / T 528 standard;

[0154] (4) Shear strength: Test the shear strength of the adhesive according to GB / T 7124 standard;

[0155] (5) Salt spray resistance test: The samples were all 150 mm × 100 mm × 1 mm steel plates. The surfaces were degreased with solvent and polished with sandpaper. The adhesives of the embodiments and comparative examples were evenly applied to the front and back surfaces and the sides of the steel plates using a thickness controller so that the adhesives completely covered the steel plates. The thickness of the adhesive was controlled at (150 ± 10) μm. The salt spray test was performed after curing for 14 days under standard test conditions (temperature (23 ± 2) °C, relative humidity (50 ± 5)%). The salt spray test was performed in accordance with GB / T1771-2007.

[0156] The test results of the adhesives prepared in the embodiments and comparative examples are shown in Table 3:

[0157] Table 3

[0158]

[0159] It can be seen from Table 3 that adding modified hexagonal boron nitride nanosheets to the adhesive can make the adhesive have good anti-salt spray performance. This is because the surface of the modified hexagonal boron nitride nanosheets in Preparation Example 1 of the present application has a variety of functional groups and is easier to disperse. The sheet structure of the modified hexagonal boron nitride can form a large-area protective layer, thereby blocking the invasion of corrosive medium ions in salt spray and achieving the effect of anti-salt spray.

[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0161] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. An adhesive composition, characterized in that: The composition comprises the following components in parts by weight: 45 to 60 parts of terminal hydroxyl polyalkylsiloxane, 2 to 6 parts of modified hexagonal boron nitride, 2 to 5 parts of a crosslinking agent, 0.1 to 1 part of a coupling agent, 40 to 50 parts of a filler, 0.5 to 1 part of a whitening powder, and 0.05 to 0.2 parts of a catalyst; Wherein, the structure of the hydroxy-terminated polyalkylsiloxane is , n is selected from a positive integer between 0 and 10; R1, R2, R3, R4, R5 and R6 are each independently selected from a C1 to C6 alkyl group; The modified hexagonal boron nitride is hexagonal boron nitride grafted with an aminosilane coupling agent; The preparation steps of the aminosilane coupling agent grafted hexagonal boron nitride include: dissolving the aminosilane coupling agent in an organic solvent to prepare a grafting solution; the mass fraction of the aminosilane coupling agent in the grafting solution is 0.5% to 3%; The hydroxylated hexagonal boron nitride and the grafting liquid are mixed in a mass volume ratio of (30 mg to 60 mg): 1 mL, and a grafting reaction is carried out at 15° C. to 30° C. to prepare the aminosilane coupling agent grafted hexagonal boron nitride; wherein the raw material for preparing the hydroxylated hexagonal boron nitride is hexagonal boron nitride powder, and the D50 particle size of the hexagonal boron nitride powder is 1 μm to 5 μm; The aminosilane coupling agent includes N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; The crosslinking agent comprises tetrabutyl ketoxime silane and vinyl tributyketoxime silane in a mass ratio of (1-2):

1.

2. The adhesive composition according to claim 1, characterized in that: The R1, R2, R3, R4, R5 and R6 are each independently selected from a methane group or an ethane group.

3. The adhesive composition according to claim 1, characterized in that: The viscosity of the terminal hydroxyl polyalkylsiloxane at 25° C. is 30,000 cps to 80,000 cps.

4. The adhesive composition according to claim 1, characterized in that: The coupling agent comprises γ-aminopropyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of (1-2):

1.

5. The adhesive composition according to any one of claims 1 to 4, characterized in that: The adhesive composition has one or more of the following characteristics: (1) The filler includes one or more of talc, calcium carbonate, barium sulfate and silicon dioxide; (2) The whitening powder includes one or more of titanium dioxide, zinc oxide, lead oxide and magnesium oxide; (3) The catalyst includes one or more of dibutyltin dilaurate and dibutyltin dichloride.

6. The adhesive composition according to any one of claims 1 to 4, characterized in that: The preparation steps of the hydroxylated hexagonal boron nitride include: The hexagonal boron nitride nanosheets are mixed with an alkaline solution and subjected to a surface hydroxylation reaction to prepare hydroxylated hexagonal boron nitride.

7. The adhesive composition according to claim 6, characterized in that: Meet one or more of the following conditions: (1) The molar concentration of hydroxyl in the alkaline solution is 4 mol / L to 6 mol / L; (2) The process parameters of the surface hydroxylation reaction include: the temperature of the surface hydroxylation reaction is 70°C~90°C.

8. The adhesive composition according to claim 6, characterized in that: The preparation steps of the hexagonal boron nitride nanosheets include: The ionic liquid is dissolved in a mixed solution of an organic solvent and water, hexagonal boron nitride is added, and ultrasonic dispersion is performed to prepare a dispersion; After centrifuging the dispersion, the supernatant was collected; After the supernatant is filtered, the hexagonal boron nitride nanosheets are prepared.

9. The adhesive composition according to claim 8, characterized in that: One or more of the following conditions are met: (1) The mass fraction of the ionic liquid in the dispersion is 3% to 6%; (2) The ionic liquid includes one or more of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium hexafluorophosphate and 1-hexyl-3-methylimidazolium hexafluorophosphate; (3) The centrifugal process parameters include: a rotation speed of 3000 r / min to 5000 r / min; (4) The filtration step uses a filter membrane with a pore diameter of 0.15 μm to 0.25 μm.

10. A method for preparing an adhesive, characterized in that: The following steps are involved: Take aminosilane coupling agent grafted hexagonal boron nitride, mix the raw material components according to the weight proportion of the adhesive composition according to any one of claims 1 to 9, and prepare the adhesive.

11. An adhesive, characterized in that: The preparation is obtained by the preparation method according to claim 10.

12. Use of the adhesive according to claim 11 in preparing photovoltaic modules.

13. A photovoltaic module, characterized in that: A cured adhesive comprising the adhesive as claimed in claim 11.

Citation Information

Patent Citations

  • Efficient mechanical method for peeling layered compounds

    CN101857195A

  • One-component alcohol sealant for photovoltaic assembly and preparation technology thereof

    CN102618209A

  • Heat-conducting insulating high polymer material composite film based on boron nitride filler and preparation method of heat-conducting insulating high polymer material composite film

    CN115572486A